Active and passive immunization against Plasmodium yoelii sporozoites. - Charoenvit, Y. (World Health Organization, 1990)
Three subunit vaccines based on the major repeat, (QGPGAP)n, and flanking regions of the Plasmodium yoelii circumsporozoite protein were designed, produced, and tested. All were immunogenic, but none gave consistent protection against a 40-200 sporozoite challenge. To demonstrate that antibodies to P. yoelii CS protein could provide protection we established a passive transfer model. Passive transfer of NYS1, an IgG3 MAb against the P. yoelii CS protein, protected 100% of mice against challenge with 5000 P. yoelii sporozoites. Binding of NYS1 to sporozoites was inhibited by incubation with (QGPGAP)2, indicating that the epitope on sporozoites recognized by this MAb was included within this peptide. The levels of antibodies to (QGPGAP)2 by ELISA, and to sporozoites by IFAT and CS precipitation reaction were similar in sera from mice that received NYS1 in passive transfer and were protected against challenge with 5000 sporozoites, and from mice that had been immunized with subunit vaccines containing QGPGAP but were not protected against challenge with 40-200 sporozoites. To determine if antibody avidity, not the absolute concentration, could explain the striking differences in protection, we established a thiocyanate elution assay. The results suggest that NYS1, the protective MAb, has a lower avidity for (QGPGAP)2 and for sporozoites than do the vaccine-induced antibodies. The data clearly demonstrate that antibodies to the CS protein can protect against intense sporozoite infection. Improved understanding of the differences between protective MAbs and non-protective polyclonal antibodies will be important in the further development of malaria vaccines.